1999
DOI: 10.5902/19805098387
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de diferentes materiais de cobertura e de um protetor físico, no estabelecimento de plantas de <i>Pinus taeda</i> L., por semeadura direta no campo.

Abstract: RESUMOEste trabalho teve como objetivo avaliar diferentes materiais de cobertura e o uso de protetor físico na implantação de povoamentos de Pinus taeda L. em semeadura direta no campo. Foram utilizados 3 materiais: vermiculita, acícula de pinus seca e picada, casca de arroz e sem-cobertura (testemunha), com e sem-protetor físico (copo plástico de 300 ml, sem fundo), com 5 repetições. A semeadura foi realizada na primeira quinzena do mês de maio de 1997, utilizando-se 3 sementes por ponto. Foram feitas analise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
1
3
0
6
Order By: Relevance
“…Protectors had different effects on plant establishment depending on the species. For Vochysia guatemalensis , they significantly improved it, in agreement with other studies that have also found enhanced plant germination (Mattei ; Mattei & Rosenthal ; Ceccon et al ) or survivorship in the first months after seeding (Serpa & Mattei ; Santos‐Júnior et al ) from the use of protectors. In contrast, we did not find any significant effects of the protectors on the establishment of Calophyllum brasiliense .…”
Section: Discussionsupporting
confidence: 90%
“…Protectors had different effects on plant establishment depending on the species. For Vochysia guatemalensis , they significantly improved it, in agreement with other studies that have also found enhanced plant germination (Mattei ; Mattei & Rosenthal ; Ceccon et al ) or survivorship in the first months after seeding (Serpa & Mattei ; Santos‐Júnior et al ) from the use of protectors. In contrast, we did not find any significant effects of the protectors on the establishment of Calophyllum brasiliense .…”
Section: Discussionsupporting
confidence: 90%
“…A semeadura direta é um método alternativo e tem apresentado resultados promissores com espécies exóticas, especialmente do gênero Pinus (Mattei, 1993;1998;Brum et al 1999;Serpa, 1999, D'Arco e Mattei, 2000. Algumas tentativas foram realizadas com semeadura direta com espécies nativas (Mattei, 1995;Schneider, 1999;Alvino et al 2001;Mello, 2001;Krohn et al 2001), também produzindo resultados animadores.…”
Section: Introductionunclassified
“…The weakness of seedlings in function to the soil compression resulted because of the less moisture observed as the principal factor of the cause of seedlings death. Serpa and Mattei (1999), observed a larger percentage of survival in plants of Pinus taeda, used for timber and cellulose originated in the interior the physical protectors. Besides, Santos-Junior et al (2004) observed an increment in the survival percentage of Tabebuia serratifolia, used for landscape and reforestation, while physical protector used for transparent plastic cups of 500 ml without bottom and buried 2 cm under the hole, was in relation to the absence of physical protector.…”
Section: Resultsmentioning
confidence: 99%
“…Different materials with different sizes, shapes and colors had been used as physical protectors by many researches (Barnett and Baker, 1991;Serpa and Mattei, 1999;Mattei et al, 2001;Klein, 2005;Klein et al, 2005;Ferreira et al, 2007). According to Carneiro (1995), those protectors must be light, non-toxic, hygroscopic and must recover all soil surface.…”
Section: Introductionmentioning
confidence: 99%